Calcium- and voltage-gated BK channels in vascular smooth muscle - Dopico, Alex M. (Pflugers Arch, 2018)
Ion channels in vascular smooth muscle regulate myogenic tone and vessel contractility. In particular, activation of calcium- and voltage-gated potassium channels of large conductance (BK channels) results in outward current that shifts the membrane potential towards more negative values, triggering a negative feed-back loop on depolarization-induced calcium influx and SM contraction. In this short review, we first present the molecular basis of vascular smooth muscle BK channels and the role of subunit composition and trafficking in the regulation of myogenic tone and vascular contractility. BK channel modulation by endogenous signaling molecules, and paracrine and endocrine mediators follows. Lastly, we describe the functional changes in smooth muscle BK channels that contribute to, or are triggered by, common physiological conditions and pathologies, including obesity, diabetes and systemic hypertension.